Investigation of Central Nervous System Dysfunction in Chronic Pelvic Pain Using Magnetic Resonance Spectroscopy and Noninvasive Brain Stimulation. Issue 5 (2nd May 2014) - Simis, Marcel; Reidler, Jay S.; Duarte Macea, Debora; Moreno Duarte, Ingrid; Wang, Xiaoen; Lenkinski, Robert; Petrozza, John C.; Fregni, Felipe
Abstract Background Recent studies demonstrate that chronic pelvic pain is associated with altered afferent sensory input resulting in maladaptive changes in the neural circuitry of pain. To better understand the central changes associated with chronic pelvic pain, we investigated the contributions of critical pain‐related neural circuits using single‐voxel proton magnetic resonance spectroscopy (MRS) and transcranial direct current stimulation (tDCS). Methods We measured concentrations of neural metabolites in 4 regions of interest (thalamus, anterior cingulate cortex, primary motor, and occipital cortex [control]) at baseline and after 10 days of active or sham tDCS in patients with chronic pelvic pain. We then compared our results to those observed in healthy controls, matched by age and gender. Results We observed a significant increase in pain thresholds after active tDCS compared with sham conditions. There was a correlation between metabolite concentrations at baseline and quantitative sensory assessments. Chronic pelvic pain patients had significantly lower levels of NAA/Cr in the primary motor cortex compared with healthy patients. Conclusions tDCS increases pain thresholds in patients with chronic pelvic pain. Biochemical changes in pain‐related neural circuits are associated with pain levels as measured by objective pain testing. These findings support the further investigation of targeted cortical neuromodulatory interventions for chronic pelvic pain.